The Effectiveness of Discovery Learning Model in Writing Descriptive Text - Widayanto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
This study is intended to describe the effectiveness of the application of discovery learning model in writing Descriptive texts. Learning process in education and training field is less related to daily life so that the participants are less passionate and bored. The learning process is still centered on the Widyaiswara/instructor (teacher centered). The problem examined in this paper is whether the discovery learning Model effective in improving the learning outcomes of training participants in the English Teacher Training class in writing Descriptive texts. This research used the Quasi experiment method, conducted at the Surabaya Religious Education and Training Center. Madrasah Aliyah Class I English teacher training class was as a control group while Madrasah Aliyah Class II English teacher training class was as an experimental group. Data obtained through four types of instruments: (1) achievement test, (2) observation, (3) interview, and (4) questionnaire. Data of test results analyzed using t-test statistics. The results showed that the discovery learning model can improve the learning outcomes of participants’ products and processes. Discovery learning model can be used as an alternative learning to write descriptive text.